2021
DOI: 10.1097/cej.0000000000000663
|View full text |Cite
|
Sign up to set email alerts
|

Association of aspirin and nonaspirin NSAIDs therapy with the incidence risk of hepatocellular carcinoma: a systematic review and meta-analysis on cohort studies

Abstract: According to the current research evidence, the therapy of nonsteroidal anti-inflammatory drugs (NSAIDs) might effectively decrease the risk of hepatocellular carcinoma (HCC) incidence. Investigations have been conducted on the relationship between NSAIDs (aspirin and nonaspirin NSAIDs) and the risk of HCC incidence. We searched the PubMed, Web of Science, Embase and Cochrane Library databases for cohort studies published prior to 15 March 2020 and screened eligible studies. There were a total of 12 eligible s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…Another study using the same database showed that aspirin and clopidogrel increase the RFS and OS of patients with HBV‐related HCC after liver resection 39 . However, a meta‐analysis on HCC recurrence after liver resection showed that aspirin alone does not reduce recurrence 52 . The present study adds to these findings by showing no association between aspirin use and survival outcomes after curative liver resection for HCC.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Another study using the same database showed that aspirin and clopidogrel increase the RFS and OS of patients with HBV‐related HCC after liver resection 39 . However, a meta‐analysis on HCC recurrence after liver resection showed that aspirin alone does not reduce recurrence 52 . The present study adds to these findings by showing no association between aspirin use and survival outcomes after curative liver resection for HCC.…”
Section: Discussionmentioning
confidence: 45%
“…39 However, a meta-analysis on HCC recurrence after liver resection showed that aspirin alone does not reduce recurrence. 52 The present study adds to these findings by showing no association between aspirin use and survival outcomes after curative liver resection for HCC. This study has some limitations.…”
Section: Discussionmentioning
confidence: 49%
“…In this retrospective study, aspirin use was associated with longer survival in patients with unresectable HCC not amenable to locoregional procedures and treated with sorafenib. Aspirin might prevent the development of HCC in at-risk patients [ 2 , 9 , 10 ], although its impact on the prognosis of patients who already developed HCC remains undefined. In this respect, patients receiving curative procedures have never been investigated, likely due to the fact that these therapies eradicate the target tumor and its recurrence is usually bound to either a de novo HCC or metastatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Èíòåðåñíûìè îêàçàëèñü ðåçóëüòàòû íåäàâíåãî àíàëèçà ðèñêà è ÷àñòîòû âûÿâëåíèÿ ãåïàòîöåëëþëÿðíîé êàðöèíîìû [41]. Îêàçàëîñü, ÷òî ÀÑÊ, íî íå äðóãèå ÍÏÂÑ, ìîaeåò çíà÷èòåëüíî ñíèçèòü ðèñê ãåïàòîöåëëþëÿðíîé êàðöèíîìû, îñîáåííî ó ïàöèåíòîâ ñ öèððîçîì ïå÷åíè èëè âèðóñíûì ãåïàòèòîì.…”
Section: ðèñê ãåïàòîòîêñè÷íîñòèunclassified